Nazirashah Enterprise: Bahulu Opah / Noor Syazana Abd Rahman… [et al.] - Abd Rahman, Noor Syazana; Norddin, Nor Athira; Wan Mohd Zain, Wan Nazihah; Mohd Fadzil, Siti Aishah (2011)
In business world, the emergent of many company will produced the variety of the products in market. Through our short survey ‘Bahulu’ is one of the potential products in market. ‘Bahulu is very popular among Malaysia peoples either they stay at village or at the town. This is because nowadays, our generations will not forget about the specialties of the ‘bahulu’ and it can maintain for a long time. If the product do not introduced to the next generation, they will not know what is ‘bahulu’ is all about in future. ‘Bahulu is very synonym with the Malay culture. This is because they make the ‘bahulu’ for their own consumption and give present to their neighbor or some of them sell it. The uniqueness of the “bahulu” is the tastes that make people want to buy it. As we know, nowadays many kinds of food are produced, but the product of ‘bahulu’ still not forgotten because many of them like to eat ‘bahulu. To make this product, we need the true technique. This is because, if we produced the product without the true technique, the product will not be as good as we want. We have to learn the technique from our great grandmother. The present market of “bahulu” is very stiff; this is because there are many people are venturing into this business. As the entrepreneur we must do our best to survive in this business and never and ever give up. We are the new in this business world and still need more knowledge to learn about the strategy on how to conduct this business well. So we prepare this business plan as our reference in running day to day business operation.